High density polyethylene (HDPE)/China clay blend / Nur Raihan Mohamed - Mohamed, Nur Raihan (2008)
The effect of China clay on the HDPE properties was studied. This studied covered the effect of maleic anhydride as the coupling agent in this blends. The specimens were fabricated at temperature 170 °C by using the compression moulding machine and cut into the bar shape according to both ASTM and ISO standard. The testing involved both mechanical and thermal testing. From the testing, it can be observed that by incorporating the China clay, the tensile strength of the HDPE was decreased. The incorporation of the coupling agent did not increase the tensile strength of the blend. However, the Young's modulus of most of the blends was increased. In the izod impact testing, impact strength of the blend that contains the 10 wt% China clay was higher than unfilled HDPE. The incorporation of China clay more than 10 wt% decreased the impact strength of the HDPE. From the FTIR testing, the appearance of the new peak represented the interaction between HDPE and China clay was observed. The formations of air bubbles during the processing were found affected the properties of the HDPE/China clay blend.